Direct Synthesis and Characterization of Zr-SBA-15 Mesoporous Molecular Sieves - Song, Guoqiang; Li, Shougao; Wang, Lisheng; Meng, Yin; Li, Fuxiang (Asian Journal of Chemistry, 2014)
This work reports the synthesis and characterization of Zr-SBA-15 mesoporous molecular sieves via direct synthesis, with Zr(NO3)4·3H2O as the zirconium source. The surface features, crystalline structure and textural properties are characterized by X-ray diffraction, nitrogen adsorption-desorption isotherms, transmission electron microscopy, thermogravimetry-differential thermal analysis and electron diffraction spectroscopy. The XRD patterns and TEM micrographs of the calcined samples show the characteristic diffraction peaks of the tetragonal ZrO2 and the ordered mesostructure in frameworks. The largest Zr/Si molar ratio during Zr-SBA-15 synthesis is 2.1. Similarly, the Brunauer-Emmett-Teller (BET) area also shows a decreasing tendency, which agrees with the XRD patterns. When the Zr/Si ratio was over 1.5, the characteristic peaks of the tetragonal ZrO2 phase can be observed. However, when the Zr/Si ratio is 1.5 or less, the samples have a high surface area (i.e., greater than 398 m2/g), with pore diameters of approximately 7.40 nm, which are within the limits for mesoporous materials.